+0

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is \frac(x^2)(A^2)-\frac(y^2)(B^

0
330
2

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is (x^2)/(A^2)-(y^2)/(B^2)=1

where A =_____

B =_____

Guest Jun 16, 2015

#2
+91454
+10

I just want to practice this for myself because I keep forgetting it.

http://web2.0calc.com/questions/the-equation-of-the-hyperbola-that-has-a-center-at-1-2-a-focus-at-4-2-and-a-vertex-at-3-2-is-frac-x-c-2-a-2-frac-y#r2

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is

$$\frac{x^2}{A^2}-\frac{y^2}{B^2}=1$$

Vertex =( 0 $$\pm$$ A, 0)    So A= 4

$$\\Focus=(0\pm \sqrt{A^2+B^2},0)\\\\ \sqrt{16+B^2}=5\\ 4^2+B^2=5^2\\ B=3$$

$$\frac{x^2}{4^2}-\frac{y^2}{3^2}=1$$

Melody  Jun 16, 2015
Sort:

#1
+18829
+10

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is (x^2)/(A^2)-(y^2)/(B^2)=1

$$\dfrac{x^2}{A^2}-\dfrac{y^2}{B^2}=1$$

vertex at (-4 , 0 ):

$$\small{\text{ \begin{array}{l} (-4,0) =(\pm A ,0)\\ A = \pm4 \end{array} }}$$

focus at (5 , 0) :

$$\small{\text{ \begin{array}{l} (5,0) =(\pm \sqrt{A^2+B^2} ,0)\end{array} }}\\ \begin{array}{rcl} A^2+B^2 &=& 5^2 = 25\\ (\pm4)^2+B^2 &=& 25\\ B^2 &=& 25-16 = 9\\ B &=& \pm 3 \end{array} }}$$

A = $$\small{\text{\pm 4}}$$

B = $$\small{\text{\pm 3}}$$

$$\dfrac{x^2}{(\pm 4)^2}-\dfrac{y^2}{(\pm 3)^2}=1$$

heureka  Jun 16, 2015
#2
+91454
+10

I just want to practice this for myself because I keep forgetting it.

http://web2.0calc.com/questions/the-equation-of-the-hyperbola-that-has-a-center-at-1-2-a-focus-at-4-2-and-a-vertex-at-3-2-is-frac-x-c-2-a-2-frac-y#r2

The equation of the hyperbola that has a center at (0,0) , a focus at (5 , 0) , and a vertex at (-4 , 0 ) , is

$$\frac{x^2}{A^2}-\frac{y^2}{B^2}=1$$

Vertex =( 0 $$\pm$$ A, 0)    So A= 4

$$\\Focus=(0\pm \sqrt{A^2+B^2},0)\\\\ \sqrt{16+B^2}=5\\ 4^2+B^2=5^2\\ B=3$$

$$\frac{x^2}{4^2}-\frac{y^2}{3^2}=1$$

Melody  Jun 16, 2015

5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details